Copper-catalyzed tandem trifluoromethylation/cyclization of internal alkynes. Issue 11 (11th November 2014) - Ji, Yun-Long; Lin, Jin-Hong; Xiao, Ji-Chang; Gu, Yu-Cheng
Abstract : Copper-catalyzed tandem trifluoromethylation/cyclization of internal alkynes with Umemoto's reagent leading to 3-trifluoromethyl-1, 2-dihydronaphthalene derivatives in moderate to good yields is described. Abstract : Copper-catalyzed tandem trifluoromethylation/cyclization of internal alkynes with Umemoto's reagent leads to 3-trifluoromethyl-1, 2-dihydronaphthalene derivatives in moderate to good yields. The utility of this copper-catalyzed tandem reaction was demonstrated by oxidizing and reducing the trifluoromethylated product to give naphthalene and tetrahydronaphthalene, respectively, and the development of a short route to a trifluoromethylated analogue of Nafoxidine.